The Use of Social Media by Female Physicians in an International Setting: A Mixed Methods Study of a Group WhatsApp Chat - Halah Ibrahim; Pascale Anglade; Sawsan Abdel-Razig (Mary Ann Liebert, 2020)
Background: The past decade has witnessed an increase in informal and bottom up driven ?she-for-she? efforts, often using social media, to promote the advancement of women in medicine. Yet, this area of research is nascent with limited information on the use of social media platforms by female physicians, especially in the international medical arena. The purpose of this study was to investigate the use of a social media platform by a diverse group of female physicians in an international setting. Materials and Methods: The study used a mixed methods approach, including quantitative descriptive statistics and qualitative thematic analysis of the content of posts of a women physicians WhatsApp group during a 1-year time period (June 1, 2018?May 31, 2019). Results: The group consisted of 122 members with 4897 posts during the 1-year time period. Nine themes were identified including requests for medical information, logistics, personal recommendations, promotion, celebration, community engagement, education, women's empowerment, and employment inquiries. Engagement was high with 72% of members posting during the last 30 days of analysis and 92% of questions posted receiving a response, often within minutes. There were no instances of unprofessional social media behavior. Conclusions: The social media platform was effective in enabling female physicians to expand networks, exchange ideas, share scientific information, celebrate accomplishments, and provide support to colleagues. Creating a social media forum for women physicians may be an effective tool to foster a network of support and community.